A novel composition for glass ionomer cements - Mustafa, Ammar A. (Kulliyyah of Engineering, International Islamic University Malaysia, 2012)
The introduction of glass ionomer cement (GIC) in the early 1970s raised much interest amongst researchers in the field of dental biomaterials as a favorable adhesive to dental tissues and to other dental materials, and due to its biocompatibility and its ability of fluoride release. However, there are problems related to its brittle nature and its low compressive and diametric tensile strength that made it unsuitable for areas of high stress. This has reduced its potential and limited its clinical applications. Therefore, a variety of new GIC formulas are investigated in this work aiming at producing materials with properties that overcome these drawbacks. New formulas with constituents of various proportions, like the AKFA1 and AKFA2 were tested; the first is based on boron oxide as a substitute to aluminum oxide, and AKFA2, which consisted of a conventional network of alumino-fluoro-silicate that has been restructured with the addition of lithium fluoride. The glass structure of the materials was ascertained by X-ray diffraction and particle size analysis. The tests performed on a variety of the test materials showed better chemical, mechanical and, physical characteristics by comparison with the control specimens taken from the conventional 3M KetacTM Cem glass ionomer cement and GC Fuji I® cement. All tests were performed according to International Standard Organization (ISO) 9917-1 2003. The chemical study included the evaluation of water solubility, pH and calcium and fluoride release. The mechanical investigations involved the estimation of bond strength to dentin, compressive strength, and diametric tensile strength. An estimation of working and setting times, film thickness measurements, showed that these materials satisfy the ISO requirements, and that they are superior to the commercially available materials.The importance of the new ingredients in the process of setting reaction, ion release and cement properties are thought to lead to new concepts. Although conventional glass theories exhibit boron oxide as a glass former agent, the results suggest that the boron oxide may act as an intermediate agent entering the network of the glass, rather than disrupting it, while lithium fluoride acts as an additional ingredient in the structure and does not necessarily as a substituting agent.